Os sete princípios da felicidade propostos por Archor e a prática dos líderes e suas equipes - Osório, Caroline (Universidade do Vale do Rio dos Sinos, 2016)
This study has the objective to understand in which ways the Seven Principles of Happiness, by Archor (2015), apply to the actions of leaders towards theis workteams. Aiming the objectives, the data gathering was done by exploratory research, through semi-structured interviews with business team leaders. The results obtained in this study demonstrated that the Seven Principles of Happiness are a reality to the interviewed leaders, even if the doctrine is unknown to them, they use it intensely in the everyday work with their teams.
Keywords: Psicologia positiva; Felicidade; Princípios da felicidade; Positive psychology; Happiness; Principles of happiness